Comparative Study of Inoculation Methods to Determine the Aggressiveness of Xanthomonas citri pv. glycines Isolates and to Evaluate the Reaction of Soybean Cultivars to Bacterial Pustule - Caroline Bertoglio; Izabela Moura Duin; Janaina Netzel de Matos; Neucimara Rodrigues Ribeiro; Rui Pereira Leite; Maria Isabel Balbi-Peña (Agronomy, 2023)
Bacterial pustule caused by Xanthomonas citri pv. glycines (syn. X. axonopodis pv. glycines) is an important bacterial disease for soybean production worldwide. Currently, the planting of resistant soybean cultivars is the main measure for control of the disease. Therefore, the objectives of this study were to determine the aggressiveness of different X. citri pv. glycines isolates and to establish a new protocol to evaluate the reaction of soybean cultivars to bacterial pustule under greenhouse conditions. The molecular analysis based on the entire 16S rRNA gene sequence revealed that the isolates GDM 01, GDM 02, 333 and 87-2 belong to the X. citri pv. glycines pathovar with 100% identity with the pathotype strain K29 of this bacterium. Differences in aggressiveness were observed among the X. citri pv. glycines isolates. There were differences in the reaction of the soybean cultivars to bacterial pustule, depending on the inoculation method. The isolates 333, GDM 01 and GDM 02 were the most aggressive, while 87-2 and GDM 03 were the least aggressive ones. The best conditions for inoculation of the soybean plants were in the V3 vegetative growth stage with the inoculum concentration of 108 CFU mL−1, and moist chamber for 24 h before and after inoculation. Spraying without injury was the quickest and most practical inoculation method to screen soybean genotypes for resistance to bacterial pustule in breeding programs. Further, this method of inoculation closely simulates the natural bacterial infection under field conditions and produces typical symptoms of the disease. The standard brush inoculation method overestimated disease severity, so we do not recommend this method for the evaluation of bacterial pustule resistance in soybean breeding programs.